A Review of the Quality of Technical Teacher Training in Uganda: Implication for Global Competitiveness - Ddungu-Kafuluma , John Mukasa (African Journal of Education,Science and Technology (AJEST), 2014)
Competent Technical and Vocational education Teachers are critical in the training of a technologically able and skilled workforce that is globally competitive and can effectively contribute to sustainable economic growth and development. For technical teachers to be globally competitive, their training has to be based on a standard curriculum, the training has to be done by well qualified instructors, in modern